RESPON PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) DI PRE NURSERY PADA PEMBERIAN DOSIS KOTORAN WALET DAN DOSIS AZOSPIRILLUM sp. - indhi azzahri (Universitas Tidar, 2025)
A research on the response to growth of oil palm ( Elaeis guineensis Jacq) seedlings in the pre-nursery with dose of swallow droppings and dose of Azospirillum sp., was carried out in September 23 - December 21, 2021 at the Oil Palm Research Center Marihat Unit, Riau. The research method used is factorial (4x4) arranged in a completely randomized design. The first factor was the dose of swallow droppings, with levels W0: 0 g/polybag, W1: 250 g/polybag, W2: 500 g/polybag, and W3: 750 g/polybag. The second factor is the dose of Azospirillum sp., with levels A0: 0 ml/polybag, A1: 10 ml/polybag, A2: 20 m/polybagl, and A3: 30 ml/polybag. The results showed that the dose of swallow manure increased the fresh weight of the crown, the dry weight of the crown, the water content of the crown, the fresh weight of the roots, and the dry weight of the roots of oil palm seedlings in the pre-nursery. Application of Azospirillum sp. can increase the number of leaf midrib, fresh weight of crown, and also the fresh weight of the roots of oil palm seedlings in pre-nursery. There is an interaction between the dose of swallow droppings and the dose of Azospirillum sp. namely on the parameters of the fresh weight of oil palm seedlings roots in the pre-nursery.